STEM-16. TRYPTOPHANYL tRNA SYNTHETASE (trpRS) FUNCTIONS AS A PRO-STEMNESS CYTOKINE DURING CHEMOTHERAPY IN GLIOBLASTOMA. (12th November 2021) - Nandoliya, Khizar; Budhiraja, Shreya; Shireman, Jack; Zolp, Andrew; Lin, Peiyu; Perrault, Ella; Park, Cheol; Baisiwala, Shivani; Pott, Sebastian; Basu, Anindita; Ahmed, Atique
Abstract: Glioblastoma (GBM) is the most common adult malignant brain tumor. Despite an aggressive standard of care involving surgical resection, radiation therapy, and temozolomide (TMZ)-based chemotherapy, GBM remains a fatal disease due to a 100% recurrence rate. Tumor heterogeneity and cell plasticity are the main contributors to GBM recurrence after treatment, and thus it is essential to study the mechanisms of therapy-induced cellular plasticity. To identify these mechanisms, we performed in vivo single-cell analysis of primary (no therapy), during therapy, and post-therapy recurrent model patient-derived xenograft model of GBM. The analysis revealed a higher transcription of tryptophanyl-tRNA synthetase (trpRS) during TMZ therapy ( p < 0.0001 ). Across multiple datasets, elevated trpRS was shown to correlate significantly with shorter GBM patient survival times ( p = 0.0069 ). TrpRS has been noted to have non-canonical functions, including the ability to be secreted and act as a cytokine in response to injury, often to upregulate stemness pathways to promote healing and regeneration. Based on this observation, we hypothesized that during TMZ treatment, trpRS secretion promotes stemness in neighboring GBM cells via activation of the phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) pathway. This study shows that in response to TMZ treatment, secreted trpRS levels are significantly elevated compared to control in multiple GBM cell lines as analyzed by western blotting. Additionally, expression of trpRS is elevated in TMZ-resistant GBM6R cells compared to TMZ-sensitive GBM6. Furthermore, phosphorylated Akt levels, indicative of the activation of the pro-stemness PI3K/Akt pathway, correlate positively with trpRS. This study, one of the few to examine genetic changes during therapy, sheds light on a novel therapeutic target for GBM.